Tourism business clusters: A tool for transforming MSEMs in the tourism industry in Tanzania - Ladislaus Batinoluho (School of Tourism, Universitas Ciputra Surabaya, 2022)
This study explores the need to consider the tourism business cluster’s approach in Tanzania to transform the tourism industry. The methodology for this study was qualitative. The study involved 114 respondents, who were randomly drawn from the sample frame of tourism businesses maintained by the tourism organizations in Tanzania. It was found that over 98 percent of the tourism MSMEs in Tanzania were not familiar with tourism value chains. Even those who seemed to understand the concept (2%) understood only the most visible sub-sectors of travel and tourism, especially at the destination level and on issues such as air, road, rail transport, accommodation, food, and beverage outlets. Over 99 percent of the tourism MSMEs operate in isolation from other sector players in Tanzania. The need for the establishment of tourism clusters is crucial in ensuring that Tanzania destination continues to be competitive.